A cross sectional study to evaluate indications and outcomes of caesarean section in a district hospital of West Bengal - Maurya, Pratima; Saini, Sandeep; Saini, Bhawna; Kumar, Mohit; Adhya, Ajit Kumar; Mondal, Ranjit Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: There is drastic rise in caesarean section (CS) rate worldwide in last decade as compared to optimal CS rate (10-15%) recommendation by WHO. This study was conducted to assess incidence and feto-maternal outcome in CS delivery. Methods: A cross-sectional study was conducted in pregnant women admitted over one year from September 2017- August 2018 in West Bengal. Demographic details and indication of CS were recorded along with documentation of feto-maternal outcomes. Statistical analysis was performed with help of Epi Info (TM) 7.2.2.2. Z-test and corrected Chi square (χ2) test. p<0.05 was considered to be statistically significant. Results: Out of total 10831 deliveries, 2914 (27%) women underwent CS. Demographic analysis shows maximum number of patients to be between 20-25years (51.7%), rural (58%), primigravida (51.3%), term pregnancy (87.7%). Non-progression of labour or NPL (45%) was most common indication of CS followed by previous CS (26.2%) and fetal distress (17.9%). Post CS wound infection was seen in 33 (1.1%) women. Two maternal deaths were recorded. Still born was documented in 0.8% while 6.8% fetus were referred to paediatric ICU. Conclusions: Rise in CS rates was mainly reported in 20-25 years age group, rural patients, in term pregnancy of primigravida patients. Most common indication for CS was NPL followed by previous CS and fetal distress. Mostly patients showed no complication in postpartum period. Only few patients had wound infection, hysterectomy and post-partum haemorrhage. More than 99% fetus survived without any complications.